+0  
 
+1
215
1
avatar

3a^+4a=2a^2-2a-9 

 

Must write in Standard Form and Solve.

Guest May 22, 2017
 #1
avatar+7324 
+1

I think this is the equation:

3a^2 + 4a = 2a^2 - 2a - 9

 

Subtract 2a^2 from both sides of the equation.

a^2 + 4a = - 2a - 9

 

Add 2a to both sides of the equation.

a^2 + 6a = -9

 

Add 9 to both sides of the equation.

a^2 + 6a + 9 = 0           \(\leftarrow\)          I think this is the standard form of the equaion.

 

Now we can factor the left side like this

(a + 3)(a + 3) = 0

(a + 3)^2 = 0

 

Take the square root of both sides.

a + 3 = 0

 

Subtract 3 from both sides of the equation.

a = -3

hectictar  May 22, 2017

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.